Exploration of students computational thinking abilities in solving sequences and series problems based on learning style - Sulistiyowati, Dewi; Masduki, Masduki (Desimal: Jurnal Matematika, 2024)
Computational thinking skills play an important role in the 21st century to help students solve math problems. One way in which students' problem-solving abilities are influenced by learning style. This research aims to explore the computational thinking abilities of students studied according to visual (V), auditory (A) and kinesthetics (K) learning styles. This research uses a qualitative method through a case study model. The researcher applies data collection instruments in the form of test questions, learning style questionnaires, and interviews. Based on the test results and the learning style questionnaire, the researcher selected 2 students from each learning style. The results of this study revealed that students with a visual style showed indicators of abstraction, pattern recognition, algorithmic thinking, and generalization. Furthermore, in students with an auditory learning style, indicators of abstraction, decomposition, pattern recognition, algorithmic thinking and generalization emerge. In kinesthetics learning style students, indicators of abstraction, pattern recognition and algorithmic thinking emerge. Based on this, the conclusion obtained is that the difference in students' learning styles has an impact on indicators of computational thinking ability in solving problems related to sequences and series.